PERAN PEMERINTAH DALAM PENGEMBANGAN POTENSI PARIWISATA DI KAWASAN PESISIR KABUPATEN BONE BOLANGO - Fenti Prihatini Tui; Rosman Ilato; Rusli Isa; Juriko Abdussamad (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to describe the Government's Role in the Development of Tourism Potential in the Coastal Area of ​​Bone Bolango Regency, using a qualitative descriptive method and approach. To obtain data used data collection techniques in the form of interviews, observation and documentation. As for the data validation techniques include credibility tests (extended observations, increased persistence and triangulation), transferability (external validity), reliability, and confimability. The data analysis technique used is an interactive model consisting of reduction, data presentation and conclusion. The results of the study show that (1) the government's role as a regulator is not optimal even though there are regulations, but the implementation of tourism has not been well managed. (2) The government's role as a dynamicator is optimal, this is indicated by the existence of programs organized by the Tourism and Creative Economy Office of Bone Bolango Regency which are carried out routinely every year so that they have an impact on improving services for visiting tourists at every tourist attraction in Bone Bolango District. (3) The government's role as a facilitator has been optimal, this can be seen by the existence of various programs including the provision of Information Technology-based tourism marketing facilities, and (4) The government's role as a catalyst in accelerating the development of regional potential even though it has been implemented but has not been optimal. This is caused by the rejection of the business community towards government policies regarding the application of retribution taxes to tourist attractions.